Effectiveness of Humor Appeal in Advertisements of Fast Moving Consumer Goods (FMCGs) - Puranik, Rakshita (Indian Journal of Marketing, 2011)
Advertising is a tool of marketing, which is used to influence and attract the customer as its aim is to create awareness, arouse interest and push sales advertising in a way by which a company communicates with its customers - both current and potential. In ancient times, the most common form of advertising was word of mouth, wall or rock painting for commercial advertising, and slowly, it became the most widely used component of a firm's promotional strategy. Effectiveness contributes significantly to the productivity of the advertisers in terms of allocation of budgets. Advertising Effectiveness is an evaluation of the extent to which a specific advertisement or advertising campaign meets the objectives specified by the advertisers. This paper studies the effectiveness of humor appeal in advertising of FMCGs, as many companies are using humor appeal to attract the audience for their product. This study is an attempt to identify the factors which influence the effectiveness of humor appeal in the advertisements of FMCG. For the study, standardized scale was administrated on a sample of 100 respondents from Indore (Madhya Pradesh), India in the year 2008. The statistical tools were used to arrive at the results - and factors were identified that can help the advertisers in choosing a right mix to make an advertisement humorous.